The Effect of Curcumin on the Antioxidant System in Diabetic Rats - SALGINTAŞ, HH; DÖNMEZ, N; ÖZSAN, M (Journal of the Hellenic Veterinary Medical Society, 2022)
The aim of this study was to determine the effect of oral administration of curcumin, also known as a highly effective antioxidant, which has been used as a spice in experimental diabetic rats with streptozotocin (STZ) on antioxidant system. In this research, 30 healthy adult male Wistar albino rats, were used. The animals were divided into four groups as control group (K), diabetes group (D), curcumin group (C), and diabetes + curcumin group (DC). In order to create diabetes, D and DC groups were administered 60 mg/kg STZ as a single dose by intraperitoneal injection. Curcumin (50 mg/kg live weight/day) was given orally to the C and DC groups. At the end of the experiment, Malondialdehyde (MDA), Superoxidedismutase (SOD), Glutathione (GSH), Catalase, and glucose levels were determined. The MDA level was significantly higher in the D group compared to the other groups. MDA level determined in DC group was found to be significantly lower from group D (p <0.05) while getting closer to groups K and C. It was also found that the levels of antioxidants SOD, GSH and catalase which are known to be effective against oxidative stress, were significantly apparently lower in group D compared to control groups (K and C). Again from the perspective of these parameters, when the data in group DC were evaluated, it was observed that the obtained data were getting closer to K and C or becoming similar. The blood glucose level obtained from the D group was significantly higher than the other groups. As a result, the data obtained from the research shows that curcumin, which is used in experimental diabetes-induced rats for its antioxidative and antidiabetic effects, is very helpful thanks to the positive effect in terms of the parameters followed.